The role of issue familiarity and social norms: findings on new college students’ alcohol use intentions - Rajiv N. Rimal; Saar Mollen (Journal of Public Health Research, 2013)
Background. Scholars in a variety of disciplines are interested in understanding the conditions under which social norms affect human behavior. Following the distinction made between descriptive and injunctive norms by the focus theory of normative conduct, the theory of normative social behavior predicts that the influence of descriptive norms on behavior is moderated by injunctive norms, outcome expectations, and group identity. We extended the theory by testing the proposition that the influence of descriptive norms on behavior would be greater under conditions of greater issue familiarity, defined as the ease with which one can cognitively access the behavior or behavioral issue. Design and Methods. The model was tested in the domain of alcohol consumption intentions by conducting a survey among incoming students (n=719) to a large university in the United States. Data indicated that students in the sample were well representative of the university population. Results. The influence of descriptive norms on behavioral intentions was moderated by issue familiarity, as predicted. Familiarity was a facilitator of behavior: the influence of descriptive norms on behavioral intentions was greater under conditions of high, rather than low, familiarity. The overall model explained 53% of the variance in alcohol consumption intentions. Conclusions. Public health interventions promoting health behaviors need to take into account the extent to which the behaviors are familiar to the target audience. The influence of norms appears to be weaker when the behavior is unfamiliar or novel. Implications for theory and interventions for reducing alcohol consumption are discussed.